2016
DOI: 10.1080/10410236.2015.1089398
|View full text |Cite
|
Sign up to set email alerts
|

Meeting Weight Management Goals: The Role of Partner Confirmation

Abstract: Social support research suggests romantic partners could play a vital role in the success of individuals' weight management (WM) efforts, but contradictory findings from previous research have impeded our understanding of how romantic partners influence weight management goal attainment. Employing a confirmation perspective, overweight participants (body mass index [BMI] greater than 25) who were actively trying to manage their weight (N = 53) were asked to respond to daily questionnaires for a period of 2 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 50 publications
3
24
0
Order By: Relevance
“…First, challenge is more germane to contexts of physical activity. CT research has demonstrated that exercise patterns are uniquely explained by receiving challenge from a variety of sources, including mothers (Dailey et al, 2014), romantic partners (Dailey et al, 2016), and a host of significant others (Dailey et al, 2010). Further, coaches are evaluated largely on their ability to offer challenge to athletes (Becker, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…First, challenge is more germane to contexts of physical activity. CT research has demonstrated that exercise patterns are uniquely explained by receiving challenge from a variety of sources, including mothers (Dailey et al, 2014), romantic partners (Dailey et al, 2016), and a host of significant others (Dailey et al, 2010). Further, coaches are evaluated largely on their ability to offer challenge to athletes (Becker, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The broadness of this proposition allows for the selection of appropriate outcomes of confirmation based upon a given relationship and/or context. To date, CT has been applied to a variety of interpersonal relationships and topics including how confirmation shapes individuals’ weight management (Dailey, Crook, Glowacki, Prenger, & Winslow, 2016; Dailey, McCracken, et al, 2011; Dailey, Thompson, & Romo, 2014), adolescents’ identity development (Dailey, 2010), and young children’s social adjustment (Munz & Wilson, 2014). These studies have indicated that developmental messages from a collection of significant others (Dailey, McCracken, et al, 2011; Dailey, Romo, & Thompson, 2011) and mothers (Dailey et al, 2014) are deemed effective when infused with challenge and acceptance.…”
Section: Review Of Literaturementioning
confidence: 99%
See 3 more Smart Citations